Cervical lenght as a predictor of preterm delivery: gestational agerelated percentiles vs fixed cut-offs - Gramellini, D.; Fieni, S.; Kaihura, et al., C. (Acta Biomedica Atenei Parmensis, 2007)
Background: To determine whether preterm delivery is more effectively predicted by sonographic cervical length measurement using fixed cut-off or gestational age-specific percentiles. Methods: One hundred and eight patients hospitalized for suspected preterm labor (PTL) were studied prospectively between the 20th and the 33rd week of gestation. Results: Cervical length below 15 mm, 25 mm and the 2.5th centile showed substantially equivalent odds ratios for delivery within 7 days (7.5, 7.6, and 7.1, respectively), while for delivery before the 34th week the odds ratios varied between 3.6 with cervical length